THU0099 Cardiovascular MR (CMR) Evidence for Reduced LV Mass in Rheumatoid Arthritis (RA), Suggesting Pathology Other than Atherosclerosis for Heart Failure. (15th July 2016) - Bissell, L.-A.; Erhayiem, B.; Hensor, E.M.; Fent, G.; Burska, A.; Donica, H.; Plein, S.; Buch, M.H.; Greenwood, J.P.; Andrews, J.
Abstract : Background: An increased risk of heart failure in RA exists 1 . Aetiology is unclear with some evidence that cardiomyopathy may occur early in RA, from pathology distinct to atherosclerosis 3 . Large well characterised CMR-RA studies to investigate pathogenesis are few 2 . Objectives: To evaluate sub-clinical CVD in an asymptomatic-CVD established RA cohort compared to healthy controls (HC), using reference standard CMR-measured outcomes & novel CMR-measures of carotid artery. Methods: 76 ACR1987 RA patients (pts) with dis.>5yrs, no CVD/diabetes, assessed for CV traditional risk factor (TRFs)/RA profile, pulse wave velocity (PWV), non-contrast 3T CMR (heart & carotids) reported by CMR-cardiologists, compared to 26 HC. Carotid measures inc. mean (MWT) & maximum (MxWT) wall thickness, wall (WVol) & luminal (LVol) volume & WVol-index (WVol-I, WVol/(WVol+LVol)). UVA variables (var.)=TRFs, BMI, waist/hip ratio (WHR), HOMA-IR, NTproBNP, dis. duration (ddur), 3vDAS28, ACPA, HAQ-DI, joint surgery hx, biologic use & PWV. MVA var.=age/sex/known associated (ass.) var./UVA r>0.3. Results: Mean (SD) age (yrs) of RA pts; 60 (9.2), 74% female; HC 52 (11.4), 54% female. Median (IQR) ddur 16.5 (10.7, 25.7)yrs, 81% ACPA+ve, DAS28CRP 2.59 (1.30, 3.33), 67% on biologic. There were no significant differences in lipids/glucose/HOMA-IR between RA/HC. Trend for higher NT-proBNP in RA seen. In MVA (inc. age/sex), increasing ddur ass. with NTproBNP (0.5% rise in NTproBNP per 1% increase in ddur, p0.034). RA pts (after adj. for age/sex/TRFs) had reduced LVmass/BSA, LVEF, native T1 values & increased strain (Mid-S') vs HC; no difference seen for LVEDV, LVESV, SV, LVmass/EDV, torsion or arterial stiffness (PWV/distensibility). No significant differences in carotid measures between RA/HC seen. In RA pts, 10yr JBS2 CV risk score correlated with WVol (r0.377 p=0.004) & LVol (r0.441 p=0.001). TRFs ass. with cardiac & carotid measures in RA. Conclusions: CMR evidence for reduced LV mass in RA, suggesting pathology other than atherosclerosis as the cause of heart failure; perhaps microvascular dysfunction. TRFs, not RA features, are important determinants of CMR measures of subclinical CVD in RA. References: ArthRheum 2005;52:412–20 EULAR 2015 OP0163 A&R 2010:62v4 Disclosure of Interest: None declared